Characteristics of temporomandibular joint structures after mandibular condyle fractures revealed by magnetic resonance imaging - Kim, Bong Chul (Maxillofac Plast Reconstr Surg, 2016)
BACKGROUND: This study aimed to evaluate the structural changes of temporomandibular joint immediately after condylar fractures with magnetic resonance imaging (MRI). METHOD: We evaluated 34 subjects of condylar fractures with MRI. The position, shape, and signal intensity of the condyle, disc, and retrodiscal tissue were analyzed with MR images. RESULTS: Immediately after trauma, the disc was displaced with the fractured segment in almost all cases. And, the changes of signal intensity at the retrodiscal tissue were found but less related to the degree of fracture displacement. And, the high signals were observed almost at all fractured joint spaces and even at some contralateral joints. CONCLUSIONS: The displaced disc as well as the increased signal intensity of the joint space, condylar head, and retrodiscal tissue demands more attention to prevent the possible sequela of joint.